PENGARUH KONDISI SISTEM DRAINASE, PERSAMPAHAN DAN AIR LIMBAH TERHADAP KUALITAS LINGKUNGAN (Studi kasus Kelurahan Kuningan Kecamatan Semarang Utara) - Oktiawan, Wiharyanto; Amalia, Setia (Universitas Diponegoro, 2012)
Kelurahan Kuningan in the district of north Semarang meet with enviromental quality and people’s healthy degree decrease cause by poor drainage system, solid waste and waste water management. This case had been caused several disease that disturb people’s healthy. The purposes of this research was to know the existing condition of drainage system, solid waste and waste water in KelurahanKuningan, to know the influence of existing condition into enviromental quality and people’s healthy, to give an overcoming solution connected with PenyehatanLingkunganPemukiman program that points on people in this development area. Method used in this research is observation, questionaire and interview, BOD concentration measurement in drainage line and secondary data collection include institution aspect, operational, financial, law and also people’s role. Results of this research show that BOD concentration in tertiary, secondary and primary drainage line is over from PP No.82 tahun 2001. Calculation results show the available pump is not enough to take the water debit from domestic rain that accumulated with domestic waste water, plus when the flood tide and flood from the higher area. The condition is getting worse by stucking trash in line that causing disease and become sediment. Waste water distribution system in this area is not appropriate with high density population and also public MCK as sanitation place is careless. That case caused the unclean enviromental and people have to expend extra money to take the medicine and to buy clean water. The recommended overcoming solutions are formating the pumping team and public MCK team management, increasing pumping capasity, maintenance budget, exploiting the sediment, 3R program, waste water distribution system with communal system and public MCK fixed up.